2021
DOI: 10.1007/s12668-021-00867-w
|View full text |Cite
|
Sign up to set email alerts
|

Very Selective Detection of Low Physiopathological Glucose Levels by Spontaneous Raman Spectroscopy with Univariate Data Analysis

Abstract: After decades of research on non-invasive glucose monitoring, invasive devices based on finger blood sampling are still the predominant reference for diabetic patients for accurately measuring blood glucose levels. Meanwhile, research continues improving point-of-care technology toward the development of painless and more accurate devices. Raman spectroscopy is well-known as a potentially valuable and painless approach for measuring glucose levels. However, previous Raman studies deal with glucose concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Five consecutive spectra were obtained using different droplets to compute the standard deviation error bars. The previously optimized data pre-process pipeline was implemented 28 . Briefly, the autofluorescence-induced baseline was subtracted for each spectrum using the asymmetric least-square fit.…”
Section: Methodsmentioning
confidence: 99%
“…Five consecutive spectra were obtained using different droplets to compute the standard deviation error bars. The previously optimized data pre-process pipeline was implemented 28 . Briefly, the autofluorescence-induced baseline was subtracted for each spectrum using the asymmetric least-square fit.…”
Section: Methodsmentioning
confidence: 99%
“…The following supporting information [2,7,17,28,34,45, can be downloaded at: https://www.mdpi.com/article/10.3390/bios14010012/s1. Author Contributions: A.G., conceptualization, data curation, formal analysis, investigation, methodology, project administration, resources, software, supervision, validation, visualization, writingoriginal draft, writing-review and editing; L.T., data curation, formal analysis, software, writingreview and editing; A.B., supervision, writing-review and editing; S.C., conceptualization, funding acquisition, project administration, resources, supervision, writing-review and editing.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Notable among these advancements is the emergence of optical Raman-scattering-based biochemical sensing (Raman biosensing) as a rapidly evolving approach in remote healthcare, offering a compelling alternative to biorecognitionbased biosensing methodologies [25,26]. Raman biosensing capitalizes on its inherent selectivity by exploiting the distinct chemical signatures of biomolecules to generate unparalleled characteristic fingerprint spectra [27,28]. Compared to traditional biosensing techniques reliant on biorecognition elements, in our earlier study, we have shown that Raman biosensing delivers superior performance marked by label-free monitoring capabilities, stable recording, high accuracy, and remarkable long-term operation capability in 90-day long experimentation in multiplexed biomarker detection without requiring temperature or pH calibration [7].…”
Section: Introductionmentioning
confidence: 99%
“…Blood is more commonly used than saliva and tears as MUT for electromagnetic-based glucose sensors. In [83,84,137], Raman Spectroscopy was applied. A linear relation was observed between the signal intensities and the glucose concentration difference in [83].…”
Section: Non-invasive Sensor Principlesmentioning
confidence: 99%